Comparison of Consumer Interest in Telkomsel and Tri Providers Case Study in Unimed Digital Business - Nasution, Mutiara Akbar; Fitri, Anisa; Safitri, Nurdina; Ramadhan, Novan Ananda (Lembaga Riset Mutiara Akbar (LARISMA), 2023)
This study aims to compare consumer interest in choosing Telkomsel and Tri providers. A total of 41 respondents who have experience using both cellular providers were taken as samples using an online survey method. The data obtained were analyzed using a t-test to compare the average consumer interest scores in four aspects, namely price, network quality, customer service, and internet speed. The results of the study showed that overall, consumer interest in choosing Telkomsel was higher than Tri. Telkomsel was considered better in several aspects than Tri. This study provides an overview of consumer preferences in choosing a cellular provider. In conclusion, this study shows that product and service quality are important factors in influencing consumer interest in choosing a cellular provider. This study can be a reference for both providers to improve the quality of customer service, network quality, prices offered, and internet speed to meet consumer needs.